Regional stability and integration processes - Yarash Gaffarov (Universitas Muhammadiyah Sidoarjo, 2019)
The integration processes help address global and regional issues in the political, economic, legal and socio-cultural spheres, aimed at ensuring the national interests of these countries, international peace, stability, security and cooperation, mutual trust and goodwill among the public. It is the summarizing process of the gradual formation of the internationalized system